2014
DOI: 10.3109/14767058.2014.991711
|View full text |Cite
|
Sign up to set email alerts
|

Obstetrical outcomes in patients with early onset gestational diabetes

Abstract: Most patients diagnosed with early onset gestational diabetes do not have undiagnosed type 2 diabetes but do have unique characteristics and obstetrical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
7
1
Order By: Relevance
“…Consistent with our findings, women with presumed undiagnosed type 2 diabetes were more often multiparous. These women also had a higher baseline HbA 1c and more often had a glucose challenge test ≥11.1 mmol/l [12]. In another study, women diagnosed with GDM of <12 weeks gestation were compared with women with preexisting diabetes [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with our findings, women with presumed undiagnosed type 2 diabetes were more often multiparous. These women also had a higher baseline HbA 1c and more often had a glucose challenge test ≥11.1 mmol/l [12]. In another study, women diagnosed with GDM of <12 weeks gestation were compared with women with preexisting diabetes [11].…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies have not looked at the outcomes of women specifically with undiagnosed type 2 diabetes, several studies have compared women with GDM diagnosed early (<24 weeks gestation) with those diagnosed in the usual time. Women diagnosed with GDM of <24 weeks gestation tended to be older, were more likely to be multiparous, had a higher BMI, and reported a family history of diabetes [12]. In a recent meta-analysis of 13 cohort studies comparing outcomes in early vs. late-onset GDM, women diagnosed earlier had higher perinatal mortality and neonatal hypoglycaemia, and required more insulin [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies have compared the treatment outcomes between women with eGDM and preexisting diabetes. Both studies found that results in the eGDM group despite early diagnosis and treatment approximated those seen with preexisting DM [ 115 , 116 ].…”
Section: Interventional Studies In Egdmmentioning
confidence: 99%
“…However, there is a lack of data on mental health outcomes during pregnancy and in the postpartum in women with eGDM. Concerning metabolic health in the postpartum period, we are aware of a few, mostly retrospective studies that showed higher rates of abnormal glucose tolerance in the postpartum in women diagnosed with eGDM compared to cGDM (22)(23)(24). However, the overall low postpartum testing rates of around 50% limit the interpretation of their findings and they do not comment on cardiovascular risk factors.…”
Section: Introductionmentioning
confidence: 99%